Analysis of three-dimensional endocardial and epicardial strains from cardiac magnetic resonance in healthy subjects and patients with hypertrophic cardiomyopathy. - Zhao, Xiaodan; Tan, Ru San; Tang, Hak Chiaw; Leng, Shuang; Zhang, Jun-Mei; Zhong, Liang (Medical & Biological Engineering & Computing, 2018)
Hypertrophic cardiomyopathy (HCM) is a genetic disease that leads to left ventricle (LV) hypertrophy with or without the presence of LV outflow tract obstruction. The aim of this study was to find an easy and useful indicator based on cardiac magnetic resonance (CMR) images for control subjects and patients with and without obstruction. CMR scans were performed for 19 control subjects and 19 HCM patients. Endocardial strain was defined as [Formula: see text], with [Formula: see text] being the length of endocardium at end-diastole (end-systole); similarly for epicardial strain ([Formula: see text]). The strains were evaluated in cine CMR two-, three- and four-chamber views. Six atrioventricular junction (AVJ) points from three CMR views were semi-automatically tracked. The peak systolic velocity (Sm1), peak early diastolic velocity and late diastolic velocity (Em, Am) were extracted and analysed. Compared with control subjects, HCM patients had significantly smaller three-dimensional strains and AVJ motion incorporating measurements from three long-axis views (all P < 0.05). Moreover, ROC analysis found that three-dimensional global epicardial strain <17.2% had the best sensitivity 94.4% and specificity 94.7% to differentiate HCM from control (AUC = 0.97). Therefore, three-dimensional endocardial and epicardial strains provide an easy and effective approach to manage and triage hypertrophic cardiomyopathy patients.